Comprehensive analysis of mortality risk factors in low-grade B-cell lymphoma - Tong-Yoon Kim; Gi-June Min; Seok-Goo Cho; Seoree Kim; Jong Hyuk Lee; Byung-Su Kim; Joon Won Jeoung; Hye Sung Won; Youngwoo Jeon (PLoS ONE, 2026)
Background Low-grade B-cell lymphomas (LGBCLs) account for approximately 40% of non-Hodgkin lymphomas with low progression. LGBCL is divided into subgroups, which share common complications. Analyzing prognostic factors and mortality causes could improve patient survival; however, currently available models present limitations in discriminating the cause of death. Therefore, this study aimed to compare the prognostic factors and causes of death, such as secondary malignancies (SMs), aggressive histologic transformation (HT), and infectious complications, including coronavirus disease 2019 (COVID-19), in LGBCLs using a competing risk analysis. Methods This retrospective analysis included 1,047 adults with LGBCLs (follicular lymphoma, 689; marginal zone lymphoma, 312; mantle cell lymphoma [MCL], 46) diagnosed between January 2011 and December 2022 across seven centers. Competing risk models were employed to estimate cumulative incidence rates of lymphoma progression-related and non-lymphoma-related mortality. Results Patients with SMs (3.8%) exhibited poorer overall survival than those without SMs, whereas HT and COVID-19 status did not impact survival outcomes in multivariate analysis. Analysis revealed an association of SMs, age > 60 years, male sex, pleural effusion, and elevated lactate dehydrogenase levels with worse non-lymphoma-related mortality. Moreover, age > 60 years, MCL, nodal MZL, and anemia were linked to poorer outcomes for lymphoma progression-related death. Conclusions The management of non-lymphoma-related risk factors, such as through early SM detection, is crucial for improving the survival of patients with LGBCLs.